Membentuk Pemimpin Masa Depan Melalui Pelatihan Pengelolaan Keuangan - Saragih, Susanti; Margaretha, Yolla; Kristine, Fanny; Margaretha, Meily; Nursalin, Kezia Kurniawati; Sherlywati, Sherlywati; Kuswoyo, Chandra (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service initiative aims to support educational institutions in fostering the social and emotional development of adolescents by promoting awareness of saving, enhancing understanding of personal finance concepts, and equipping adolescents with essential financial skills to navigate future financial challenges. Methodology: The methodology employed in this initiative involved simulations and role-playing activities structured as a training program. The training focuses on the "Gerakan SMART" (Simpan, Mengurutkan kebutuhan, Atur pengeluaran, Realisasikan, dan Tercatat), a framework designed to assist individuals in creating, managing, and effectively utilizing personal finances. Results: A total of 97 junior high school students participated in this study. Evaluation based on three key indicators revealed that the community service activity was successful in achieving its objectives. The "Gerakan SMART" game improved the participants’ knowledge of financial management. Conclusion: Financial management is a crucial skill for adolescents, preparing them to face future financial challenges and ensuring their well-being. Training programs focused on financial management for young people are expected to cultivate future leaders equipped to thrive in competitive workplace environments that demand these skills, thereby contributing to the achievement of the Sustainable Development Goals (SDGs). Limitations: Owing to time and resource limitations, the program had difficulty ensuring that participants fully understood the material and assessing the training’s long-term effects. Contribution: By promoting the "Gerakan SMART" framework, the program equips young generations with the tools to navigate future financial challenges and prepares them to be leaders in the future.